HUBUNGAN SOCIAL SUPPORT DENGAN DEPRESI ORANG TUA YANG MEMPUNYAI ANAK KECANDUAN GADGET - Hindyah Ike Suhariati; Endang Yuswatiningsih (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Gadgets play a major role in the development of the times and help humans in completing all kinds of matters better. Starting from learning, looking for entertainment, to communicating with others. However, the impact of using this gadget too often is certainly not good, both for health and mental impact. The low level of social support received by parents of children who are addicted to gadgets is a trigger for parental depression at various levels and symptoms. The purpose of this study was to determine the relationship between social support and depression in parents who have children addicted to gadgets at Candimulyo Elementary School, Jombang Regency. The design of this study uses a cross-sectional design. The population in this study were all parents who had children at SDN 1 Candimulyo, Jombang Regency, as many as 160 people with a sampling technique using simple random sampling and a sample of 104 people. Data processing editing, coding, scoring, tabulating. The data analysis used was univariate and bivariate analysis with the Rank Spearman statistical test. with alpha (0.05). The results showed that almost half of the parents of addicted children received low social support, with a total of 36 people (34.6%), while almost half of the depression levels experienced major depression, with some 46 people (44.2%). The results of statistical tests using the Spearman Rank test obtained a value of p = 0.000, if α = 0.05 then p <α which means H1 is accepted. In conclusion, there is a relationship between social support and depression in parents who have children addicted to gadgets